God of adventure : exploring how God teaches through adventure and calls us to do the same - Dunning, Bruce A., 1957- (Belleville, Ont. : Essence Pub., 2012)
"Adventure is extensively used as a teaching tool throughout the Bible. In God of Adventure Bruce Dunning proposes 19 principles from the Bible that outline the validity, core concepts and teaching approaches of Christian adventure learning." --from back cover.
Issued also in an electronic format.
Keywords: Risk-taking (Psychology) -- Religious aspects -- Christianity; Christian life